Análisis bromatólogico de Vasconcellea pulchra V.M. Badillo y Vasconcellea x heilbornii V.M. Badillo procedentes de la provincia Bolívar, Ecuador. - Matute Jaramillo, Lizeth Patricia (2013)
Vasconcellea pulchra and Vasconcellea x heilbornii are shrubs and trees respectively, endemic and native of southern Ecuador growing at an altitude between 1986 m and 2336 m. They are in the provinces of Loja, Bolívar and Pichincha, commonly known as sacha col and chamburo. The nutritional components of ripe fruits were analyzed by proximate analysis. They were collected on the farm Masabanda, belonging to Tres Marias community in the province of Bolivar. The assembly was held at the Salesian University and its identification in the National Herbarium of Ecuador by Dr. Carlos Ceron and Dr. Efrain Freire, who corroborated his scientific identification.